New Chalcone-Derived Molecule for the Topical Regulation of Hyperpigmentation and Skin Aging - Alfredo Martínez-Gutiérrez; Alexandra Bertran; Teresa Noya; Eloy Pena-Rodríguez; Susana Gómez-Escalante; Sergio Pascual; Luis Shotze Luis; Mari Carmen González (MDPI AG, 2024)
Background/Objectives: Skin hyperpigmentation is a biological process that results in an excessive production of melanin and is highly regulated by several mechanisms, tyrosinase being one of the key enzymes involved. Current reported inhibitors lack clinical efficacy, show toxic side effects, have poor bioavailability, or low formulation compatibility. The aim of this study was to design a new effective tyrosinase inhibitor for topical hyperpigmentation and anti-aging treatments. Methods: Homology modeling was used to build the tridimensional structure of human tyrosinase, and virtual docking was used to predict molecule-enzyme binding modes. The tyrosinase activity of the designed and synthesized compounds was assessed and water solubility was determined by HPLC. Cell assays were performed to determine melanin content, cytotoxicity, wound healing, anti-glycation, antioxidation, and autophagy efficacy. Gene expression and miRNA levels were quantified by qPCR and chromatin accessibility by ATAC-Seq. Human reconstructed epidermis was used to test the depigmenting efficacy as well as the skin irritation potential. Results: The 3D structure of human tyrosinase was designed and validated. The new molecule could effectively inhibit human tyrosinase and melanin synthesis in 2D monocultures and a 3D epidermis model. Two melanogenesis-related miRNAs were increased in treated cells. Anti-glycation, antioxidant, mitochondria protection, autophagy activation, and wound healing properties were also observed, with special emphasis on epigenetics. Conclusions: The designed molecule is a potential candidate to be used as a depigmenting and anti-aging agent, with suitable properties to be introduced in final product formulations for dermatology or cosmetics treatments.